EMBLICA EXTRACT INDUCES TYPE I PRO-COLLAGEN SYNTHESIS AND INHIBITS COLLAGENASE ACTIVITY IN MOUSE FIBROBLASTS - Luanpitpong, S.; Chanvorachote, P.; Pongrakhananon, V.; Nimmannit, U. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Decrease of type I collagen generation as well as the increase of its degradation via matrix metalloproteinases (MMPs; e.g. gelatinases and collagenases) are considered as a major cause of skin aging. A potent natural antioxidant exblica extract from emblica fruits (Phyllanthus emblica) was herein evaluated for collagen promoting activity in mouse fibroblasts. We demonstrated that the level of intracellular type I pro-collagen increased following emblica extract treatment in concentration-dependent manner. Emblica extract at the concentration of 100 µg/mL exhibited the maximum effect on type I pro-collagen; approximately 7 fold-induction versus non-treated control determined by Western blot analysis. Moreover, our result indicated that emblica extract affected the MMPs function. Percentage of collagenase inhibition exceeded forty at the concentration of 100 µg/mL of emblica extract. Taken together, emblica extract has a promising anti-aging effect attributed to its positive effect on type I collagen formation as well as the protection against collagen degradation.